Positive Protection: Protecting Genetic Resources Related to Traditional Knowledge in Indonesia - Rohaini Rohaini; Nenny Dwi Ariani (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
Genetic Resources is a foundation of human life, as a source of food, industrial raw materials, pharmaceuticals, and medicines. From its utilization may provide a financial benefit to the provider and the user of it. Unfortunately, most of it obtained from developing countries through biopiracy, including Indonesia. Furthermore, in the early 1980s, access and benefit sharing (ABS) to genetic resources became an international issue. It leads to the adoption of the Convention on Biological Diversity (CBD) in 1992. However, since it was approved, the whole ideas of excellence of it could not be implemented, a problem on it still arises. Intellectual property right laws, in certain aspects, are possible for using to protect traditional knowledge from their utilization. However, at the same time, intellectual property regime also becomes “a tool” to legitimate of biopiracy practices. Due to massive international pressure, mostly in developing countries, it proposes two kinds of protections, which are positive protection and defensive protection. This paper will examine one of it, which is positive protection. By using the normative method and qualitative approach, this paper identified at least two kinds of positive protections that we can develop to protect genetic resources related to traditional knowledge, which are optimizing the patent law and developing the sui generis law. Furthermore, it can be done by some revision by adding new substances, an improvement on the articles, or even by doing the deletion on certain articles. Moreover, in order to develop the sui generis law, it identified several minimum elements that shall be contained on it, inter alia: the purposes of protection; scope of protection; criteria of protection; the beneficiaries of protection: the holder of traditional knowledge; the kind of rights to be granted; how the rights acquired; how to enforce it; how the rights lost or expired; and dispute resolution.  Keywords: Positive Protection, Genetic Resources, Traditional Knowledge.